Pengaruh Stres Kerja terhadap Kinerja Karyawan Bagian Mengolah pada UMKM Ikan Giling Karyani Sungsang - Tiara Aqnes; Agustina Hanafi; M. Ichsan Hadjri (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
This research aims to determine the effect of work stress on the performance of employees in the processing division at Ikan Giling Karyani Sungsang MSME. The variables used in this research are work stress as the independent variable and employee performance as the dependent variable. The population in this research were all 40 employees of the Processing Division at Ikan Giling Karyani Sungsang MSME, as well as 1 MSMEs head who assessed employee performance. This research used a saturation sampling technique, collected primary data via questionnaires, and used simple linear regression analysis as a data analysis technique. To validate the data, the validity test, reliability test, simple linear regression analysis, correlation coefficient analysis (r), coefficient of determination (R2), and t test were used in this research. The Statistical Package for Social Science (SPSS) version 21 program assistance tool was used to analyze the data. The findings of this research show that work stress has a significant negative impact on the performance of employees in the processing division at Ikan Giling Karyani Sungsang MSME. Keywords: Work Stress, Employee Performance